The metabolites from traditional Chinese medicine targeting ferroptosis for cancer therapy - Yu Tang; Ying Zhuang; Chuanxiang Zhao; Shuangshuang Gu; Junya Zhang; Shiqi Bi; Ming Wang; Lei Bao; Mei Li; Wei Zhang; Liqun Zhu (Frontiers Media S.A., 2024)
Cancer is a major disease with ever-increasing morbidity and mortality. The metabolites derived from traditional Chinese medicine (TCM) have played a significant role in combating cancers with curative efficacy and unique advantages. Ferroptosis, an iron-dependent programmed death characterized by the accumulation of lipid peroxide, stands out from the conventional forms of cell death, such as apoptosis, pyroptosis, necrosis, and autophagy. Recent evidence has demonstrated the potential of TCM metabolites targeting ferroptosis for cancer therapy. We collected and screened related articles published in or before June 2023 using PubMed, Google Scholar, and Web of Science. The searched keywords in scientific databases were ferroptosis, cancer, tumor, traditional Chinese medicine, botanical drugs, and phytomedicine. Only research related to ferroptosis, the metabolites from TCM, and cancer was considered. In this review, we introduce an overview of the current knowledge regarding the ferroptosis mechanisms and review the research advances on the metabolites of TCM inhibiting cancer by targeting ferroptosis.